Evaluation of default mode network in temporal lobe epilepsy patients and healthy subjects: a preliminary result - Shuhada, J.M.; Husbani, M.A.R.; A I A, Hamid; Muhammad, A.R. (2020)
The default mode network (DMN) is thought to be impaired in epileptic patients, where the functional integrity of its core regions compromised. Fourteen healthy participants and fourteen aged and gender-matched patients with temporal lobe epilepsy (TLE) took part in this study. The resting-state fMRI (rsfMRI) imaging protocol was executed using a 3-T Phillips Achieva MRI scanner at the Department of Radiology, HUSM. The TLE patient displays decreased activation clusters in precuneus and supramarginal gyrus compared to the healthy group. However increased activation clusters were found on middle frontal gyrus, superior temporal gyrus, and angular gyrus compared to healthy subjects. The result from random effects (RFX) on healthy TLE revealed that the left middle frontal gyrus, bilateral superior temporal gyrus, bilateral precuneus, and right supramarginal gyrus were significantly activated but the NOV survive was so small. The findings suggested that TLE patients suffer from impairment in some DMN region, which may cause certain neuropsychological and cognitive degradation.